2008
DOI: 10.1021/jf801597t
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Monolinolein as a Substrate for Conjugated Linoleic Acid Production by Bifidobacterium breve LMC 520 of Human Neonatal Origin

Abstract: This study was designed to isolate bifidobacteria from human intestines that efficiently converts monolinolein, a monoglyceride form of linoleic acid, into conjugated linoleic acid (CLA), as well as to optimize culture conditions for improving CLA production during milk fermentation. Among 150 screened neonatal bifidobacteria, Bifidobacterium breve LMC 520 showed the highest CLA-producing ability and was tested with different types of fat substrates at various concentrations to determine the optimal conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…7 In our previous study, we found that this bacterium had very specific activity in the isomerization of LA. The objectives of this study were to identify the structure of CLnA isomer produced by B. breve LMC 520 and to optimize CLnA production from α-LNA in a comparison to CLA production by the same microorganism.…”
Section: ■ Introductionmentioning
confidence: 83%
“…7 In our previous study, we found that this bacterium had very specific activity in the isomerization of LA. The objectives of this study were to identify the structure of CLnA isomer produced by B. breve LMC 520 and to optimize CLnA production from α-LNA in a comparison to CLA production by the same microorganism.…”
Section: ■ Introductionmentioning
confidence: 83%
“…23 Among the 150 screened bifidobacteria from human intestines, only 9 strains showed the capacity to produce CLA. The GC method was also used by Kishino et al in screening of CLA-producing strains.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Studies have shown that strains of B. breve could be used as starter cultures for the development of functional milk products with high concentrations of bioactive lipids such as CLA (61)(62)(63)(64)(65)(66). Conversions of linoleic acid into CLA up to 74% were obtained using three strains of B. breve (ZL12-28, 29M2 and M7-70) isolated from breast milk (62).…”
Section: Fermentationmentioning
confidence: 99%